Diagnóstico socioeconómico de propietarios de microemprendimientos de servicios de alimentación del sector centro de la ciudad de Daule, provincia del Guayas, Ecuador. - Yépez Arévalo, Jhon Jairo (2023)
The objective of this degree Project was to conduct a socioeconomic analysis of microenterprises in the central sector of the canton of Daule, province of Guayas to understand its reality, where through the theoretical review it was possible to verify the scarce information and monitoring of this growing productive area in various sectors beyond the traditional rice sector. A documentary research was carried out to learn about the background of the problem, analyzing the previous situation of the enterprises in Ecuador at a general historical level and the impact of COVID 19; likewise, the basic concepts of the terms related to entrepreneurship and a review of the current situation of the sector. The methodology used for the socioeconomic analysis was a mixed descriptive approach using techniques and instruments such as observation, surveys and interviews; this resulted in an analysis based on surveys on socioeconomic criteria in the downtown sector of Daule and the development of a FODA matrix on the reality of microenterprises. It was concluded that the sector is in potential growth, but microenterprises have many challenges due to the economic situation of the country, investment difficulties and changes in their processes by implementing technologies.